Treatment strategies and treatment-related adverse events in MG according to the age of onset - Moura, João; Fernandes, Joana; Lima, Maria João; Sousa, Ana Paula; Samões, Raquel; Martins Silva, Ana; Santos, Ernestina (Frontiers in Neurology, 2024)
Introduction Early-onset (EOMG) and late-onset (LOMG) are distinct groups of MG patients. It is unclear if treatment strategies and treatment-related adverse events may differ according to the age of MG onset. Methods This single-center retrospective study includes all MG patients followed at a tertiary center since 2007. We reviewed the electronic clinical records. Results In total, 212 patients were identified, 142 (67.0%) females, with a median disease duration of 10 years. The median age of symptom onset was 42.0 (26.0–64.5) years, with 130 (61.3%) EOMG cases and 82 (38.7%) LOMG. EOMG were more frequently female, had longer disease duration and often more generalized MG (p < 0.001). Comorbidities were significantly more frequent in LOMG (67.1%) compared to EOMG (53.1%) (p = 0.002). Steroid-related adverse effects motivating the switch to steroid-sparing agents (82.0%) were different between groups, with hypertension, hypercholesterolemia, diabetes mellitus and malignancies being more common in LOMG. At the same time, osteoporosis and dyspepsia were more frequent in EOMG (p < 0.001). The most common first-line choice was azathioprine (45.8%), and rituximab was used in 4 patients (1.9%). Conclusion Our study shows that treatment modalities are similar between EOMG and LOMG, while steroid-related adverse events appear to be distinct.